Nonviolent utopias: heroes transgressing the gender binary in the Matrix Resurrections - Porter, Andy; Albrecht, Jessica (Feminist Media Studies, 2024)
The Matrix franchise constructs its narrative and aesthetic elements using a global frame of reference, drawing on many film genres to build its cyberpunk world and heroes. Despite the original film’s utopian visions, The Matrix fell short of its promises in favour of traditional Hollywood ideals, including binary gendered relations and an individualistic hero. The issue was further compounded with The Matrix Reloaded (2003) and The Matrix Revolutions (2003) and their irresolution of the trilogy’s central man versus machine conflict. With The Matrix Resurrections (2021), the franchise is able to shift its focus and re-present its heroes as inversions of traditional gender norms. This paper explores The Matrix Resurrections’ deviations from the original trilogy and proposes a re-reading of “The Matrix” and its heroes as embodying a nonviolent, queer utopia. Strengthened through its religious narratives, the film reconstructs Neo’s heroic masculinity and presents Trinity as his inseparable counterpart, with both characters attaining heroism through their mastering of the body. Resurrections is ultimately able to depict a utopian vision beyond gender binaries and fulfil the promises set out with The Matrix (1999).
Created from Fastlane, Scopus look-up
Keywords: cyberpunk; masculinity; nonviolence; religion; The Matrix